Influence of “Not Too Young To Run” Campaign Social Media Messages on Youth Political Participation in Nigeria - Toyosi Khadijat Owoyale; Onaopepo Ibrahim Bamidele; Ojetola Adetola Afolabi; Muhammad Ridwan (Polit Journal Scientific Journal of Politics, 2024)
Today's generation of young people is the largest the world has ever known, half of the global population is under the age of 25, and young people between the ages of 15-25 constitute one-fifth of this total. Yet, young people are starkly underrepresented in government and politics at virtually every level. The "Not too Young to Run" campaign on social media uses platforms such as Instagram and Twitter to effectively mobilize social support to reduce the age limit for running for elected office in Nigeria. Digital Generative Multimedia Tool Theory (DGMTT) was used in this study. The explanatory research design was adopted, and Google form questionnaire was utilised in collecting data. The population of this study is the Lagos Island youth of Lagos state Nigeria and the purposive sampling was used to determine the sample size of 300 respondents. The responses of the questions were analyzed using frequency tables, and simple percentage method. The findings of this works how that social media played a vital role in spreading and creating awareness for the “Not Too Young to Run” campaign. The study recommended that since the social media is the preferred medium to reach the youths, more campaigns should be done on social media on the benefits of political participation in Nigeria.